2016
DOI: 10.1038/srep32667
|View full text |Cite
|
Sign up to set email alerts
|

Competition between members of the tribbles pseudokinase protein family shapes their interactions with mitogen activated protein kinase pathways

Abstract: Spatio-temporal regulation of intracellular signalling networks is key to normal cellular physiology; dysregulation of which leads to disease. The family of three mammalian tribbles proteins has emerged as an important controller of signalling via regulating the activity of mitogen activated protein kinases (MAPK), the PI3-kinase induced signalling network and E3 ubiquitin ligases. However, the importance of potential redundancy in the action of tribbles and how the differences in affinities for the various bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…Our data also show that by doubling m Trib1 expression, we removed the requirement for an external stimulus to up-regulate OLR1 expression and the consequent clinical sequelae. The phenotype observed in response to this rise in m Trib1 expression fits well with earlier computational modeling studies that indicated that relatively modest changes in TRIB1 would have a major impact on the activity of mitogen-activated protein kinase pathways; thus, defining the concentration of these proteins is critical for shaping cell function ( 31 ).…”
Section: Discussionsupporting
confidence: 82%
“…Our data also show that by doubling m Trib1 expression, we removed the requirement for an external stimulus to up-regulate OLR1 expression and the consequent clinical sequelae. The phenotype observed in response to this rise in m Trib1 expression fits well with earlier computational modeling studies that indicated that relatively modest changes in TRIB1 would have a major impact on the activity of mitogen-activated protein kinase pathways; thus, defining the concentration of these proteins is critical for shaping cell function ( 31 ).…”
Section: Discussionsupporting
confidence: 82%
“…The pseudokinase TRIB2 acts as scaffold protein and mediates ubiquitination of substrates ( 27 ). Thereby TRIB2 negatively regulates MAPkinase signaling ( 31 ), the cascade that is a hallmark of R848-stimulated APCs. The qRT PCR analyses in Figure 3 A show that TRIB2 is significantly downregulated in R848-stimulated APCs and the Western blot data (Figure 3 B) confirm that result on protein level.…”
Section: Resultsmentioning
confidence: 99%
“…The TRIB C-terminal tail is defined by two unique sequences: the HPW[F/L] and DQXVP[D/E] motifs near the extreme N and C-terminal regions of the C-tail, respectively (Figure 4A). The HPW[F/L] motif is involved in binding of MEK1 (and other MAPKK dual-specificity kinases) to TRIB pseudokinases 46, 47, 48, whereas the DQXVP[D/E] motif is intimately involved in COP1 binding in all TRIB proteins 49, 50 and required to drive tumorigenesis in leukemia models [51]. Although these motifs are not observed in the C-terminal tail of other protein kinases, they are predicted to engage with the TRIB pseudokinase domains in a manner analogous to canonical, well-studied protein kinases, such as PKA and MAP kinases, which utilize these flanking regions to drive regulatory mechanisms involved in kinase activation and substrate phosphorylation (Figure 4B).…”
Section: A Unique C-terminal Regulatory Region In Trib Pseudokinasesmentioning
confidence: 99%